Fiber Supplements Derived From Sugarcane Stem, Wheat Dextrin and Psyllium Husk Have Different In Vitro Effects on the Human Gut Microbiota - Gamage, Hasinika K. A. H.; Tetu, Sasha G.; Chong, Raymond W. W.; Bucio-Noble, Daniel; Rosewarne, Carly P.; Kautto, Liisa; Ball, Malcolm S.; Molloy, Mark P.; Packer, Nicolle H.; Paulsen, Ian T. (Frontiers in Microbiology, 2018)
There is growing public interest in the use of fibre supplements as a way of increasing dietary fibre intake and potentially improving the gut microbiota composition and digestive health. However, currently there is limited research into the effects of commercially available fibre supplements on the gut microbiota. Here we used an in vitro human digestive and gut microbiota model system to investigate the effect of three commercial fibre products; NutriKane™, Benefiber® and Psyllium husk (Macro) on the adult gut microbiota. The 16S rRNA gene amplicon sequencing results showed dramatic fibre-dependent changes in the gut microbiota structure and composition. Specific bacterial OTUs within the families Bacteroidaceae, Porphyromonadaceae, Ruminococcaceae, Lachnospiraceae and Bifidobacteriaceae showed an increase in the relative abundances in the presence of one or more fibre product(s), while Enterobacteriaceae and Pseudomonadaceae showed a reduction in the relative abundances upon addition of all fibre treatments compared to the no added fibre control. Fibre-specific increases in SCFA concentrations showed correlation with the relative abundance of potential SCFA-producing gut bacteria. The chemical composition, antioxidant potential and polyphenolic content profiles of each fibre product were determined and found to be highly variable. Observed product-specific variations could be linked to differences in the chemical composition of the fibre products. The general nature of the fibre-dependent impact was relatively consistent across the individuals, which may demonstrate the potential of the products to alter the gut microbiota in a similar, and predictable direction, despite variability in the starting composition of the individual gut microbiota.